Political Economy of Multi-Level Tax Assignments in Latin American Countries : Earmarked Revenue Versus Tax Autonomy - Brosio, Giorgio (IMF Working Papers; Working Paper ;, 2008)
A weakness of decentralization and overall tax reforms in Latin America is the lack of attention to adequate taxation at the subnational government. A reliance on shared taxes with extensive earmarking leads to weak subnational accountability and soft budget constraints. The paper explores the options for expanding subnational taxation in Latin America. A range of subnational tax instruments might be considered, but interactions between new tax assignments and the system of transfers is important from a political economy perspective.